Accountability : a public law analysis of National Health Service contracts - Davies, A (1999)
The thesis takes as its subject the concept of accountability. It examines the use made of the concept in the public law literature, and advances a novel analytical model of the individual accountability mechanism. The model identifies the essential features of that mechanism: setting standards against which an account can be judged; requiring the person being called to account to explain and justify his or her actions; judging the account rendered against the standards set; and responding to the account rendered, where appropriate, with enforcement measures. This analytical approach provides a way of examining, in detail, an individual accountability mechanism, and identifying the main practical problems faced by the parties to it. The approach is applied to an empirical case study of National Health Service (NHS) contracts. (The fieldwork involved an examination of contractual relationships between purchasers (Health Authorities and GP fundholders) and providers (NHS Trusts) in three sample areas, using document analysis, interviews and observation.) The study's main findings fall into three groups. Firstly, purchasers were subject to various pressures and constraints (of time and resources, for example) which affected their actions in calling providers to account. Secondly, the study uncovered some of the complexities of the relationship between the parties to the accountability process. Analytical models of the accountability relationship were developed in order to classify different types of relationship according to the parties' behaviour and their degree of mutual trust. Thirdly, the study examined whether purchasers, as callers to account, could render the accountability process effective. For various reasons, purchasers often lacked the authority to set and enforce the standards they required. The model of the accountability mechanism developed in the thesis also has evaluative potential. Drawing on the public law literature as well as the empirical data, a notion of the good accountability process is evolved. This includes, for example, requirements of maximising the accountability achieved within available resources, maintaining good relationships by using fair procedures, and finding ways of making the whole process effective. Some of these principles may be of more general application to other accountability processes. Possible generalisations are explored, particularly the contribution of the thesis to the development of an explicitly public law concept of contract.